HUBUNGAN ANTARA SOSIAL EKONOMI KELUARGA DENGAN STATUS GIZI PADA PELAJAR DI SMP WILAYAH KECAMATAN MALALAYANG 1 KOTA MANADO (PHARMACON, 2016)
HUBUNGAN ANTARA SOSIAL EKONOMI KELUARGA DENGAN STATUS GIZI PADA PELAJAR DI SMP WILAYAH KECAMATAN MALALAYANG 1 KOTA MANADO Karla F. Rompas1), Maureen I. Punuh1), Nova H. Kapantow1) 1)Fakultas Kesehatan Masyarakat UNSRAT Manado, 95115 Â  ABSTRACT Poverty and malnutrition are interrelated phenomena, so that people's nutritional status is closely related with efforts to improve the economy. The nutritional status in North Sulawesi in 2010 aged 6-12 years consists of very thin 2,1%, thin 5.4%, fat 6.4%, while in 2013 very thin increased by 4%, thin 7,2%, fat 10,8% and very fat 8,8%.This reasearch use analitic observation method with cross sectional approach conducted in January-March 2016 on students in SMP Spektrum Malalayang Manado and SMP Kristen Lahai Roi Malalayang Manado. Total populat ion in this research is 94 students. Data were analyzed using Spearman correlation test at the significance level 95% (Î± = 0,05).Based on statistical analysis using Spearman correlation test, Father's level of education r= 0,085 with value p as big as 0,415 (> 0,05) maternal education r= 0,129 with value p 0,214(> 0,05) the number of dependents r= 0,034 with value p 0,745 (p>0,05) the amount of family income r=0,424 with value p 0,000 (p 0,05) pendidikan Ibu r= 0,129 dengan nilai p 0,214(> 0,05) jumlah tanggungan keluarga r= 0,034 dengan nilai p 0,745 (p>0,05) jumlah pendapatan keluarga r=0,424 dengan nilai p 0,000 (p